The mediating effect of brand trust on social media marketing-brand loyalty relationship in Mineral Water industry - Najib, Hafizhun; Yasri, Yasri (Marketing Management Studies, 2025)
This study aims to analyze the effect of social media marketing on brand loyalty of Aqua mineral water in Padang City with brand trust as a mediating variable. Using quantitative methods with hypothesis testing at the 5% significance level, the results showed that social media marketing has a positive effect on brand loyalty, strengthened by consumer trust. This study recommends the importance of monitoring the effectiveness of social media content using digital metrics, and invites further research to explore other factors that influence brand loyalty. The findings contribute to academics and practitioners in understanding marketing strategies in the digital age.